Fabians Flanieren und der Müßiggang in der Krise - Benedikt Hengstl (Recherches Germaniques)
Jakob Fabian, the protagonist of Erich Kästner’s 2013 novel Der Gang vor die Hunde [Fabian. Die Geschichte eines Moralisten, 1931], is examined in this article as a pessimistic idler, a flâneur experiencing a crisis. Fabian’s position in the society of the late Weimar Republic is understood as a reaction to the completely rationalized, economized character of the depicted world—especially Berlin—and to the experiences of an entire generation. It becomes clear that a fulfilling existence as a ‘good-for-nothing’ is no longer possible in the contemporary context. Moreover, the examination of the impressions Fabian gained on his forays through Berlin and his hometown not only allows us to grasp his perception of the crisis-ridden nature of the times, but also contributes to outlining the literary type of the unemployed white-collar worker.